Structure and Biological Evaluation of Novel Cytotoxic Sterol Glycosides from the Marine Red Alga Peyssonnelia sp. - Lin, An-Shen (2010)
Bioactivity-guided fractionation of the extract from a Fijian red alga Peyssonnelia sp. led to the isolation of two novel sterol glycosides 19-O-β-d-glucopyranosyl-19-hydroxy-cholest-4-en-3-one (1) and 19-O-β-d-N-acetyl-2-aminoglucopyranosyl-19-hydroxy-cholest-4-en-3-one (2), and two known alkaloids indole-3-carboxaldehyde (3) and 3-(hydroxyacetyl)indole (4). Their structures were characterized by 1D and 2D NMR and mass spectral analysis. The sterol glycosides inhibited cancer cell growth with mean IC(50) values (for 11 human cancer cell lines) of 1.63 and 1.41 µM for 1 and 2, respectively. The most sensitive cancer cell lines were MDA-MB-468 (breast) and A549 (lung), with IC(50)s in of 0.71–0.97 µM for 1 and 2. Modification of the sterol glycoside structures revealed that the α,β-unsaturated ketone at C-3 and oxygenation at C-19 of 1 and 2 are crucial for anticancer activity, whereas the glucosidic group was not essential but contributed to enhanced activity against the most sensitive cell lines.